Research progress on the application of Baduanjin exercise in elderly patients with chronic obstructive pulmonary disease at stable stage (八段锦在老年慢性阻塞性肺疾病稳定期患者中的应用研究进展) - ZHAO Pei (赵培); ZHANG Xi (张西); QU Renying (曲仁莹); ZHANG Hong (张红); YUAN Chen (袁晨); LI Kexin (李可心); WANG Mengdi (王梦迪); CHEN Xu (陈旭); LIU Pin (刘品); ZHAO Mingyang (赵明阳) (中西医结合护理, 2024)
Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung disease, and quality of life of COPD patients can be severely impaired with increasing severity of disease. As a kind of exercise in Traditional medicine, Baduanjin Qigong is an aerobic exercise which is suitable for elderly patients. It can improve the cardiopulmonary function of patients and is conducive to the rehabilitation of COPD. This article summarized the effective intervention of Baduanjin Qigong exercise therapy on elderly patients with COPD in stable stage, and provided reference for modify the exercise prescription for elderly patients with CODP. (慢性阻塞性肺疾病(COPD)是临床老年患者常见呼吸系统疾病, 严重影响老年患者的生活质量。八段锦动作柔和缓慢, 属于有氧运动, 且不受场地限制, 适用于老年患者, 可改善其心肺功能, 有利于COPD的康复。本研究从老年COPD稳定期患者开展八段锦运动锻炼的效果、作用机制及运动方案进行综述, 以期为老年COPD患者运动处方的修订提供参考。)